Diseño y construcción de una máquina semiautomática para corte de papas a la francesa. - Espinosa Cajamarca, Jhenry Isaías (2018)
This thesis consists in the design and construction of a semiautomatic french fries cutting machine. It intends to facilitate to the people to carry out this style of cut, considering that the elaboration of potatoes fries is a widespread activity in Ecuador. Several methods used to carry out the needed cut were described in the theoretical framework of project. People´s needs were established, listing functions and evaluation criteria applied to the solutions alternatives generated. Of the different mechanical systems considered as alternatives of solution to carry out the needed cut and after the respective analysis, the connecting rod system was selected as the best option. After obtaining in experimental form the force of needed cut (56 Kg) it was followed with the detailed design of the machine, using the corresponding theory, in addition, SAP2000 and CADE Simu programs. Once built with 304 stainless steel and polyethylene, the conditions and sequence for the correct operation were established; in the test carried out its correct functioning and capacity of 1 cut every 2 seconds were verified. Finally, the total cost of the machine was determined on basis of the values incurred for its realization and calculated the period of recovery of the investment.